2019
DOI: 10.1016/j.scitotenv.2018.09.330
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope analyses revealed the influence of foraging habitat on mercury accumulation in tropical coastal marine fish

Abstract: Bioaccumulation of toxic metal elements including mercury (Hg) can be highly variable in marine fish species. Metal concentration is influenced by various species-specific physiological and ecological traits, including individual diet composition and foraging habitat. The impact of trophic ecology and habitat preference on Hg accumulation was analyzed through total Hg concentration and stable isotope ratios of carbon (δ13C) and nitrogen (δ15N) analyses in the muscle of 132 fish belonging to 23 different specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 95 publications
(131 reference statements)
0
16
0
Order By: Relevance
“…Top predators using coastal ecosystems are known to feed on different food webs (Bird et al, 2018), inducing exposure to different sources and concentrations of contaminants (Le Croizier et al, 2016, 2019b. To characterize dietary resources, nitrogen and carbon stable isotopes (δ 15 N and δ 13 C) are traditionally used in ecotoxicological studies (Le Bourg et al, 2019;Le Croizier et al, 2020), reflecting respectively the trophic position (Pethybridge et al, 2018) and foraging habitat (Bird et al, 2018) of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Top predators using coastal ecosystems are known to feed on different food webs (Bird et al, 2018), inducing exposure to different sources and concentrations of contaminants (Le Croizier et al, 2016, 2019b. To characterize dietary resources, nitrogen and carbon stable isotopes (δ 15 N and δ 13 C) are traditionally used in ecotoxicological studies (Le Bourg et al, 2019;Le Croizier et al, 2020), reflecting respectively the trophic position (Pethybridge et al, 2018) and foraging habitat (Bird et al, 2018) of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the slope of the linear regression between THg and δ 15 N (0.34), used as measurement of biomagnification across food webs (Kidd et al, 1995), was higher than those observed by Al-Reasi et al (2007) in Gulf of Oman (0.07), Muto et al (2014) in the Santos continental shelf (0.13), and Di Beneditto et al (2012) (0.25) and Kehrig et al (2013) (0.21) in the same region as our study. Although biomagnification studies in tropical marine ecosystems are limited, this range (0.07-0.34), already observed by Lavoie et al (2013) in tropical marine food webs, reflects the different composition and vertical position in the water column (higher Hg bioavailability in the bottom sediment for benthic/demersal organisms) of the tropical food webs and/or differences in the growth rate of organisms (Muto et al, 2014;Le Croizier et al, 2019). It is already known that the biomagnification of Hg can vary greatly between marine ecosystems (Cossa et al, 2012), or even between environments of the same ecosystem (Cresson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation might occur in ariids in the adjacent marine waters of the PSR estuary in accordance with the findings of other authors that suggest that larger and/or older fish have higher THg concentrations due to longer exposure and the difficulty of eliminating mercury, as THg has a very slow excretion rate due to the metal's high affinity for thiol groups that constitute the protein fraction of the muscles (Nakao et al ., 2007). Second, the elevated assimilation of species closely related to the bottom sediment, that provides higher Hg bioavailability than the water column (Muto et al ., 2014; Le Croizier et al ., 2019), by G. genidens ( Callinectes sp. – highest THg in prey and P. porosissimus – highest THg in prey fishes) and A. luniscutis (Sciaenidae fish) resulted in the higher THg than in B. bagre .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations